I think it's the answer C, because in the second and third pairs, the -2 are the same.
Answer:
x = 1, y = 6
or
x = 5, y = 2.
Step-by-step explanation:
y=x2−7x+12
y=−x+7
Substitute for y in the first equation:
- x + 7 = x^2 - 7x + 12
x^2 - 7x + x + 12 - 7 = 0
x^2 - 6x + 5 = 0
(x - 1)(x - 5) = 0
x = 1, 5.
When x = 1, y = -1 + 7 = 6.
when x = 5, y = -5+7 = 2.
1. Horizontal asymptotes: None
Vertical asymptote: x=-2
RD: 2
Domain: First picture
Range: first pic
2.HA: y=1
VA: x= -5 negative
RD: x= 5 no negative
Domain: second pic
Range second pic
3.HA: y=0
VA: x=-4,4
RD: none
D: 3rd pic
R: 3rd pic
4.HA: none
VA: x=3
RD: x=-2
D: 4th
R: 4th
I hope this helps!!!!!!!
Answer:
Step-by-step explanation:
P1 = (2000, 1000) in the form (x1,y1)
P2 = (2012, 3400) in the form (x2,y2)
m = (y2-y1 / x2-x1)
m = ( 3400-1000 ) / (2012 - 2000)
m = 2400 / 12
m = 200
y = 200x + 800